2010
DOI: 10.1111/j.1461-9563.2010.00481.x
|View full text |Cite
|
Sign up to set email alerts
|

Dimethoate, fenvalerate and their mixture affects Hylyphantes graminicola (Araneae: Linyphiidae) adults and their unexposed offspring

Abstract: 1 Mixtures of organophosphorus and pyrethroid insecticides are widely used to combat resistance in agricultural pests, although few studies have been conducted on the effects of pesticide mixtures on beneficial nontarget organisms. 2 In the present study, we exposed adult females (F 0 ) of Hylyphantes graminicola (Araneae: Linyphiidae) to fenvalerate, dimethoate and their commercially available 1 : 1 mixture (by mass). We investigated the acute toxicity of these pesticides to the exposed adults, as well as sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 58 publications
1
20
1
Order By: Relevance
“…Our results showed that a low dose of imidacloprid might cause an increase of CarE activity and lead to an increase in the prey-capture ability of P. pseudoannulata. AChE is a target enzyme of organophosphate and carbamate insecticides (Peng et al 2010). Here, we found that P. pseudoannulata had lower AChE activity when treated with imidacloprid, and these results were negatively related to their higher susceptibility to the insecticides that were tested.…”
Section: Resultssupporting
confidence: 50%
See 3 more Smart Citations
“…Our results showed that a low dose of imidacloprid might cause an increase of CarE activity and lead to an increase in the prey-capture ability of P. pseudoannulata. AChE is a target enzyme of organophosphate and carbamate insecticides (Peng et al 2010). Here, we found that P. pseudoannulata had lower AChE activity when treated with imidacloprid, and these results were negatively related to their higher susceptibility to the insecticides that were tested.…”
Section: Resultssupporting
confidence: 50%
“…In this experiment, the spiders surviving after 5 days immersed in imidacloprid were used to make the preparations for assaying the activity of enzymes. CarE activity was measured using the method described by Peng et al (2010). AChE activity was measured essentially according to the method of Ellman et al (1961), and MFO activity was measured according to Chang and Hodgson (1975).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to reduce the effects of pesticides on non-target insects, rice pest control methods need to be improved. Application of insecticide mixtures is an effective strategy to manage several insects simultaneously and possibly to reduce total insecticide use (Han et al 1993;Corbel et al 2004;Peng et al 2010). Such mixtures have been widely used to manage pests in agriculture.…”
Section: Introductionmentioning
confidence: 99%